Physician Response Time When Communicating With Patients Over the Internet - Kummervold, Per Egil; Johnsen, Jan-Are K (JMIR Publications, 2011)
BackgroundPatients want to use electronic communication to access health services more easily. Health authorities in several countries see this as a way to improve health care. Physicians appear to have conflicting opinions regarding the suitability of electronic communication in clinical settings. ObjectivesThe aim of our study was to measure how long it actually takes physicians to answer questions from patients through an electronic communication channel, and whether some of the questions are especially time consuming. MethodsWe monitored electronic patient-physician communication. A total of 1113 messages from 14 participating physicians from 7 medical offices were analyzed. The length of questions and answers, and the time physicians spent answering the questions were recorded and analyzed. ResultsPhysicians spent an average of 2.3 minutes (median 2 minutes) answering questions from patients. The patients' questions had an average length of 507.1 characters (95% CI 487.4-526.9, SD 336.2), while physicians' answers averaged 119.9 characters (95% CI 189.8-210.0, SD 172.6). The results show that the influence of patient question length on time spent responding was negligible. For the shortest 25% of the questions the answer time was 2.1 minutes (95% CI 1.9-2.3), while it was 2.4 minutes (95% CI 2.2-2.7) for the longest 25%. Even extremely long questions had a minimal impact on the time spent answering them. A threefold increase in question length from patients resulted in only an 18% increase in physician response time. ConclusionsThe study shows the potential clinical usefulness of electronic communication between patients and health care services by demonstrating the potential for saving time.